A high-resolution record of early rift development and tectonic, sedimentary and environmental conditions in an active rift basin: IODP MSP drilling in the Corinth Rift, Greece (Expedition 381) - Lisa C. McNeill; Donna J. Shillington; Jeanine Ash; Gareth D.O. Carter; Richard E.Ll. Collier; Aleksandra Cvetkoska; Paula Diz; Mai-Linh Doan; Jeremy D. Everest; Natacha Fabregas; Eugenia Fatourou; Mary Ford; et al. (Marine Geology, 2026)

Longest documented coastal migrations of shortnose sturgeon - Joseph D. Nolan; William C. Post; Ellen Waldrop; Joseph J. Facendola; Michael S. Loeffler; William Collier; Evan C. Ingram; Martin J. Hamel; Adam G. Fox (Journal of Fish Biology, 2025)
The shortnose sturgeon (SNS; Acipenser brevirostrum ) is a United States federally endangered diadromous species. Although SNS spend much of their time in riverine habitat, inter‐river migrations have been documented in northern populations. However, the inter‐river migratory behaviour and distance capabilities of southern SNS are poorly understood. In this communication, we describe two SNS that migrated approximately 425 km across the coast, far exceeding the previously reported maximum coastal migration distance for the species. These observations offer critical updates for species descriptions and management regarding the coastal migration ability of SNS.

Small step in tech needed to upscale tropical island eradications - A. J. Burt; G. Harper; D. Ringler; M. Cagnato; L. A. Turnbull; J. C. Russell; A. Samaniego; T. Collier; S. Steibl; P. Carr; J. C. Daltry; A. Constance; et al. (Biological Invasions, 2025)

Impact of Hurricane Beryl on Texas beach-dune systems: Insights from drone-based LiDAR and multispectral surveys - Shuhab D. Khan; Aydin Shahtakhtinskiy; Muhammad Younas; Mikaela Garcia; Leo Collier; Michelle Leslie; Presley Greer; Nastassia Simon; Onur Karaca (Science of The Total Environment, 2025)

A pathway-based genetic score for inflammation: An indicator of vulnerability to phthalate-induced adverse neurodevelopment outcomes - Ahmed Elagali; Alex Eisner; Samuel Tanner; Katherine Drummond; Christos Symeonides; Chloe Love; Mimi LK. Tang; Toby Mansell; David Burgner; Fiona Collier; Peter D. Sly; Martin O'Hely; et al. (International Journal of Hygiene and Environmental Health, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Expanding the Food Agency Framework: A Mixed Methods Research Exploring Facilitators and Barriers to Home Meal Preparation Behavior in Urban and Rural Virginia Population - J. Yi; A. Stewart; N. Porter; D. Cladis; E. Collier; B. Davy; J. Lahne (Journal of the Academy of Nutrition and Dietetics, 2024)

Timing is everything; operational changes at a pumping station with a gravity sluice to provide safe downstream passage for silver European eels and deliver considerable financial savings - Liam J. Carter; Rosalind M. Wright; Robert E. Thomas; Jake Reeds; Leona A. Murphy; Stephen J. Collier; Oliver Evans; Henrik Baktoft; Jonathan D. Bolland (Journal of Environmental Management, 2023)

The influence of passive wedge-wire screen aperture and flow velocity on juvenile European eel exclusion, impingement and passage - Liam J. Carter; Stephen J. Collier; Robert E. Thomas; Josh Norman; Rosalind M. Wright; Jonathan D. Bolland (Ecological Engineering, 2023)

Harnessing the necessary nitrogen atom in chemical biology and drug discovery - Lewis D. Pennington; Philip N. Collier; Eamon Comer (Medicinal Chemistry Research, 2023)

A Magnetohydrodynamic enhanced entry system for space transportation: MEESST - Andrea Lani; Vatsalya Sharma; Vincent F. Giangaspero; Stefaan Poedts; Alan Viladegut; Olivier Chazot; Jasmine Giacomelli; Johannes Oswald; Alexander Behnke; Adam S. Pagan; Georg Herdrich; Minkwan Kim; et al. (Journal of Space Safety Engineering, 2023)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Food web characteristics of fish communities across degraded lakes provide insights for management in multi-stressor environments - M. A. Pingram; K. J. Collier; D. Özkundakci; J. Garrett-Walker (Aquatic Ecology, 2020)

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Traditional plant functional groups explain variation in economic but not size‐related traits across the tundra biome - H. J. D. Thomas; I. H. Myers‐Smith; A. D. Bjorkman; S. C. Elmendorf; D. Blok; J. H. C. Cornelissen; B. C. Forbes; R. D. Hollister; S. Normand; J. S. Prevéy; C. Rixen; G. Schaepman‐Strub; et al. (Global Ecology and Biogeography, 2019)
Aim Plant functional groups are widely used in community ecology and earth system modelling to describe trait variation within and across plant communities. However, this approach rests on the assumption that functional groups explain a large proportion of trait variation among species. We test whether four commonly used plant functional groups represent variation in six ecologically important plant traits. Location Tundra biome. Time period Data collected between 1964 and 2016. Major taxa studied 295 tundra vascular plant species. Methods We compiled a database of six plant traits (plant height, leaf area, specific leaf area, leaf dry matter content, leaf nitrogen, seed mass) for tundra species. We examined the variation in species‐level trait expression explained by four traditional functional groups (evergreen shrubs, deciduous shrubs, graminoids, forbs), and whether variation explained was dependent upon the traits included in analysis. We further compared the explanatory power and species composition of functional groups to alternative classifications generated using post hoc clustering of species‐level traits. Results Traditional functional groups explained significant differences in trait expression, particularly amongst traits associated with resource economics, which were consistent across sites and at the biome scale. However, functional groups explained 19% of overall trait variation and poorly represented differences in traits associated with plant size. Post hoc classification of species did not correspond well with traditional functional groups, and explained twice as much variation in species‐level trait expression. Main conclusions Traditional functional groups only coarsely represent variation in well‐measured traits within tundra plant communities, and better explain resource economic traits than size‐related traits. We recommend caution when using functional group approaches to predict tundra vegetation change, or ecosystem functions relating to plant size, such as albedo or carbon storage. We argue that alternative classifications or direct use of specific plant traits could provide new insights for ecological prediction and modelling.

The fate of genes that cross species boundaries after a major hybridization event in a natural mosquito population - Mark J. Hanemaaijer; Travis C. Collier; Allison Chang; Chloe C. Shott; Parker D. Houston; Hanno Schmidt; Bradley J. Main; Anthony J. Cornel; Yoosook Lee; Gregory C. Lanzaro (Molecular Ecology, 2018)
Animal species are able to acquire new genetic material via hybridization and subsequent introgression. However, little is known about how foreign genomic material is incorporated into a population over time and what genes are susceptible to introgression. Here, we follow the closely related mosquito sister species Anopheles coluzzii and Anopheles gambiae in a sympatric natural population in Mali at multiple time points spanning a period of 25 years. During this period, we observed the temporary breakdown of mating barriers, which allowed us to explore the fate of alleles that crossed the species boundary in a natural population. Whole genome sequencing of 74 individuals revealed introgression within only 34 genes (0.26% of total genes) from A. gambiae to A. coluzzii , the majority contained within a 4 Mb region on the 2L chromosome which includes the insecticide resistance gene (AGAP004707). We designed a genotyping assay to follow 25 of the 34 introgressed alleles over time and found that all A. gambiae alleles, except four, reached a frequency of 50% in the A. coluzzii population within 4 years (~50 generations) and increased to ~80% within 6 years (~75 generations). However, the frequency of all introgressed alleles, except three, decreased to ~60% in 2016. This suggests an ongoing process of purifying selection in the population against DNA of foreign ancestry, except for alleles that are under positive selection, resulting in a complex genomic landscape . This study shows that stable introgression is limited to only specific genes even within closely related species.

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Stratigraphic correlation and paleoenvironmental analysis of the hydrocarbon-bearing Early Miocene Euphrates and Jeribe formations in the Zagros folded-thrust belt - D. Hussein; R. Collier; J. A. Lawrence; F. Rashid; P. W. J. Glover; P. Lorinczi; D. H. Baban (Arabian Journal of Geosciences, 2017)

Feeding and nutrient excretion of the New Zealand freshwater mussel Echyridella menziesii (Hyriidae, Unionida): implications for nearshore nutrient budgets in lakes and reservoirs - Hélène Cyr; Kevin J. Collier; Susan J. Clearwater; Brendan J. Hicks; Simon D. Stewart (Aquatic Sciences, 2017)

Early life traits of farm and wild A tlantic salmon S almo salar and first generation hybrids in the south coast of N ewfoundland - D. Hamoutene; J. Perez‐Casanova; K. Burt; L. Lush; J. Caines; C. Collier; R. Hinks (Journal of Fish Biology, 2017)
This study examined fertilization rates, survival and early life‐trait differences of pure farm, wild and first generation ( F1 ) hybrid origin embryos after crossing farm and wild Atlantic salmon Salmo salar . Results show that despite a trend towards higher in vitro fertilization success for wild females, differences in fertilization success in river water are not significantly different among crosses. In a hatchery environment, wild females' progeny (pure wild and hybrids with wild maternal parent) hatched 7–11 days earlier than pure farm crosses and hybrids with farm maternal parents. In addition, pure wild progeny had higher total lengths ( L T ) at hatch than pure farm crosses and hybrids. Directions in trait differences need to be tested in a river environment, but results clearly show the maternal influence on early stages beyond egg‐size differences. Differences in L T were no longer significant at 70 days post hatch (shortly after the onset of exogenous feeding) showing the need to investigate later developmental stages to better assess somatic growth disparities due to genetic differences. Higher mortality rates of the most likely hybrids (farm female × wild male hybrids) at egg and fry stages and their delayed hatch suggest that these F1 hybrids might be less likely to survive the early larval stages than wild stocks.

Saquinavir Loaded Acetalated Dextran Microconfetti – a Long Acting Protease Inhibitor Injectable - Michael A. Collier; Matthew D. Gallovic; Eric M. Bachelder; Craig D. Sykes; Angela Kashuba; Kristy M. Ainslie (Pharmaceutical Research, 2016)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

Spatial and temporal patterns of range expansion of white‐winged doves in the USA from 1979 to 2007 - Jerrod A. Butcher; Bret A. Collier; Nova J. Silvy; Jay A. Roberson; Corey D. Mason; Markus J. Peterson (Journal of Biogeography, 2014)
Aim The geographical expansion of white‐winged doves ( Zenaida asiatica ) in North America has attracted the attention of biologists and sportsmen because of their recreational and aesthetic value; however, data on factors driving the spatial spread of this species are lacking. We examined spatial and temporal patterns of range expansion for white‐winged doves along the northern edge of their geographical range from 1979 to 2007 and used a dynamic occupancy model to estimate when and where doves would be found along an expansion gradient. Location Southern half of the USA . Methods We modelled spatial variation in the range expansion of white‐winged doves from 1979 to 2007 using data from the North American Breeding Bird Surveys ( BBS ) and distance from initial population centre, area of urban land cover, and ecoregion. We used a robust design occupancy analysis to estimate species expansion rate based on a model set grounded in broad‐scale conditions likely to drive dove distribution. We evaluated our best fitting model (using Akaike's information criterion adjusted for small sample size) by comparing estimates to actual observations in 1993 and 2007 using area under the curve ( AUC ) metrics from receiver‐operating characteristic plots. Results Our spatial distribution model indicated that range expansion of white‐winged doves was primarily influenced by distance from the core population centre, with additive effects of ecoregion and land cover. In 1979, white‐winged doves were present in 12% of survey locations, whereas presence increased to 41% by 2007. Across all ecoregions, urban land cover was positively related to probability of occupancy. We evaluated our model for 1993 and 2007 by comparing derived occupancy estimates to sightings of white‐winged doves within our sample hexagons using BBS survey data. Based on high AUC statistics (> 0.85), we concluded that our model was useful for accurately predicting range expansion. Main conclusions Estimating occurrence and range expansion of white‐winged doves and other expanding/invasive avian species at large spatial scales can be effectively conducted using BBS data. Using these nationwide, long‐term survey data to relate expansion to a suite of conditions likely to drive population dynamics is an effective approach to developing predictive models of range expansion.

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Effects of flow on lateral interactions of fish and shrimps with off-channel habitats in a large river-floodplain system - K. Górski; K. J. Collier; D. P. Hamilton; B. J. Hicks (Hydrobiologia, 2014)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Sustainable roofing technology under multiple constraints: a decision-analytical approach - Z. A. Collier; D. Wang; J. T. Vogel; E. K. Tatham; I. Linkov (Environment Systems and Decisions, 2013)

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

Do productivity and disturbance interact to modulate macroinvertebrate diversity in streams? - Jonathan D. Tonkin; Russell G. Death; Kevin J. Collier (Hydrobiologia, 2013)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

CCL20 Is Associated with Neurodegeneration Following Experimental Traumatic Brain Injury and Promotes Cellular Toxicity In Vitro - Christopher C. Leonardo; James Musso; Mahasweta Das; Derrick D. Rowe; Lisa A. Collier; Shyam Mohapatra; Keith R. Pennypacker (Translational Stroke Research, 2012)

The spleen contributes to stroke induced neurodegeneration through interferon gamma signaling - Hilary A. Seifert; Christopher C. Leonardo; Aaron A. Hall; Derrick D. Rowe; Lisa A. Collier; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Metabolic Brain Disease, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Characterisation of amyloid-induced inflammatory responses in the rat retina - D. R. Howlett; S. T. Bate; S. Collier; A. Lawman; T. Chapman; T. Ashmeade; I. Marshall; P. J. B. Anderson; K. L. Philpott; J. C. Richardson; C. J. Hille (Experimental Brain Research, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

A standardised sampling protocol for robust assessment of reach‐scale fish community diversity in wadeable New Zealand streams - Bruno O David; Mark P Hamer; Kevin J Collier; Mike D Lake; Graham M Surrey; Kate McArthur; Carol Nicholson; Alton Perrie; Matthew Dale (New Zealand Journal of Marine and Freshwater Research, 2010)
The New Zealand fish fauna contains species that are affected not only by river system connectivity, but also by catchment and local‐scale changes in landcover, water quality and habitat quality. Consequently, native fish have potential as multi‐scale bioindicators of human pressure on stream ecosystems, yet no standardised, repeatable and scientifically defensible methods currently exist for effectively quantifying their abundance or diversity in New Zealand stream reaches. Here we report on the testing of a back‐pack electrofishing method, modified from that used by the United States Environmental Protection Agency, on a wide variety of wadeable stream reaches throughout New Zealand. Seventy‐three first‐ to third‐order stream reaches were fished with a single pass over 150–345 m length. Time taken to sample a reach using single‐pass electrofishing ranged from 1–8 h. Species accumulation curves indicated that, irrespective of location, continuous sampling of 150 stream metres is required to accurately describe reach‐scale fish species richness using this approach. Additional species detection beyond 150 m was rare (

Improved simulation of Australian climate and ENSO‐related rainfall variability in a global climate model with an interactive aerosol treatment - Leon D. Rotstayn; Mark A. Collier; Martin R. Dix; Yan Feng; Hal B. Gordon; Siobhan P. O'Farrell; Ian N. Smith; Jozef Syktus (International Journal of Climatology, 2010)
We assess the simulation of Australian mean climate and rainfall variability in a new version of the CSIRO coupled ocean–atmosphere global climate model (GCM). The new version, called Mark 3.6 (Mk3.6), differs from its recent predecessors (Mk3.0 and Mk3.5) by inclusion of an interactive aerosol scheme, which treats sulfate, dust, sea salt and carbonaceous aerosol. Other changes include an updated radiation scheme and a modified boundary‐layer treatment. Comparison of the mean summer and winter climate simulations in Mk3.6 with those in Mk3.0 and Mk3.5 shows several improvements in the new version, especially regarding winter rainfall and sea‐level pressure. The improved simulation of Australian mean seasonal climate is confirmed by calculation of a non‐dimensional skill score (the ‘ M ‐statistic’), using data from all four seasons. However, the most dramatic improvement occurs in the model's simulation of the leading modes of annual rainfall variability, which we assess using empirical orthogonal teleconnections (EOTs). Compared to its predecessors and several international GCMs, Mk3.6 is best able to capture the spatial pattern of the leading rainfall mode, which represents variability due to the El Niño Southern Oscillation (ENSO). Mk3.6 is also best able to capture the spatial pattern of the second rainfall mode, which corresponds to increased rainfall in the northwest, and decreased rainfall over eastern Australia. We propose a possible mechanism for the improved simulation of rainfall variability in terms of the role of interactive dust in Mk3.6. By further suppressing convection over eastern Australia during El Niño events, dust feedbacks may enhance rainfall variability there, in tune with the model's ENSO cycle. This suggests that an interactive aerosol treatment may be important in a GCM used for the study of Australian climate change and variability. Mechanistic sensitivity studies are needed to further evaluate this hypothesis. Copyright © 2009 Royal Meteorological Society

Genetic variation in PARL influences mitochondrial content - Joanne E. Curran; Jeremy B. M. Jowett; Lawrence J. Abraham; Luke A. Diepeveen; Katherine S. Elliott; Thomas D. Dyer; Lyndal J. Kerr-Bayles; Matthew P. Johnson; Anthony G. Comuzzie; Eric K. Moses; Ken R. Walder; Gregory R. Collier; et al. (Human Genetics, 2010)

Ecoregional differences in macrophyte and macroinvertebrate communities between Westland and Waikato: Are all New Zealand lowland streams the same? - I. C. Duggan; K. J. Collier; P. D. Champion; G. F. Croker; R. J. Davies‐Colley; P. W. Lambert; J. W. Nagels; R. J. Wilcock (New Zealand Journal of Marine and Freshwater Research, 2002)
We characterised water chemistry, aquatic habitat, macrophytes, and invertebrate assemblages in eight lowland streams—five in Westland, South Island, and three in the Waikato, North Island, New Zealand. Factors influencing invertebrate community structure over large (between ecoregions) and small (within an ecoregion) spatial scales were investigated. The Westland sites had generally lower nutrient concentrations, conductivity, and water clarity, and coarser substrates than the Waikato sites, reflecting differences in geological history, hydrology, and land‐use intensity. The macrophyte communities in each region were very different in species composition and structure, but seasonal abundance patterns in both regions were fairly typical of New Zealand streams in general. Alien obligate submerged macrophyte species were absent from the Westland lowland stream sites, and may partly reflect the isolated nature of this region where colonisation by asexual macrophytes would be difficult. Waikato stream invertebrate faunas were dominated by molluscs (mainly Potamopyrgus ) and crustaceans (mainly amphipods), whereas Epheme‐roptera, Trichoptera, and Coleoptera taxa dominated the Westland stream faunas. The overall structure of invertebrate assemblages appeared to be influenced by a combination of regional differences in substrate type, nutrient concentrations, water clarity, and macrophyte cover. Westland streams with more upstream pastoral development had higher proportions of molluscs than those with predominantly forested or scrub catchments. Our study suggests that large‐scale ecoregional differences may override smaller‐scale land‐use effects on lowland stream invertebrate communities, and that management strategies should be developed on an ecoregional basis for lowland stream ecosystems.

The role of dust in supplying nitrogen and phosphorus to the Southeast Mediterranean - Barak Herut; Robert Collier; Michael D. Krom (Limnology and Oceanography, 2002)
This study assesses the role of the atmospheric dry fallout as a source of new nitrogen and phosphorus to the surface Levantine seawater. Leaching experiments of inorganic nitrogen (LINO 3 − , LINH 4 + ) and phosphorus (LIPO 4 ), using SE Mediterranean surface seawater, were performed on 41 aerosol (hereafter dust) samples collected on Whatman 41 filters between April 1996 and January 1999 at Tel Shikmona, Israel and on four desert‐event dust powder samples. A geometric mean of 2.8 and 3.2 mmol NO 3 − and NH 4 + per gram of dust was leached by seawater from normal (background) dry deposition captured by the filters. Significantly lower amounts of IN with lower NH 4 + :NO 3 − ratios were leached from both the 1 2 filters and the dust powder sampled during dust events (mean of 0.18 and 0.02 mmol NO 3 − and NH 4 + per gram of dust). Similarly, relatively lower values of LIPO 4 were measured in desert type events, attributed to systematic decrease in IP solubility with increased rock/soil component. The calculated LINO 3 − and LINH 4 + fluxes were 34 and 20 mmol m −2 yr −1 from normal dry deposition, 2.5 higher than the wet IN deposition, and twice the riverine input (23 mmol m −2 yr −1 , Guerzoni et al.). This high ratio is due to the semiarid climate in this basin. The estimated flux of total dry IP was 1 mmol P m −2 yr −1 , approximately 3 times higher than the input of wet IP and somewhat lower than the estimated riverine input (1.4 mmol m −2 yr −1 , Guerzoni et al. 1999). The similarity of atmospheric and burial fluxes of P in the Levantine basin reinforces the hypothesis that the atmosphere is the dominant source of P to the sediments in the deeper parts of the basin. It was estimated that the leachable fluxes of IP and IN (dry 1 wet) can support between ~15 or ~70% (1–4 g C m −2 yr −1 ) of the new production in the SE Mediterranean, effective mainly during dust events and stratification. This input may contribute significantly to the relatively high N: P ratios in Levantine deep water (~27).

UV radiation and potential biological effects beneath the perennial ice cover of an antarctic lake - R. L. Kepner; R. A. Wharton; R. D. Collier; C. S. Cockell; W. H. Jeffrey (Hydrobiologia, 2000)

Patch- and reach-scale dynamics of a macrophyte-invertebrate system in a New Zealand lowland stream - Kevin J. Collier; Paul D. Champion; Glenys F. Croker (Hydrobiologia, 1999)